A cell wall‐anchored glycoprotein confers resistance to cation stress in Actinomyces oris biofilms. (25th March 2022) - Al Mamun, Abu Amar M.; Wu, Chenggang; Chang, Chungyu; Sanchez, Belkys C.; Das, Asis; Ton‐That, Hung
Abstract: Actinomyces   oris plays an important role in oral biofilm development. Like many gram‐positive bacteria, A. oris produces a sizable number of surface proteins that are anchored to bacterial peptidoglycan by a conserved transpeptidase named the housekeeping sortase SrtA; however, the biological role of many A. oris surface proteins in biofilm formation is largely unknown. Here, we report that the glycoprotein GspA—a genetic suppressor of srtA deletion lethality—not only promotes biofilm formation but also maintains cell membrane integrity under cation stress. In comparison to wild‐type cells, under elevated concentrations of mono‐ and divalent cations the formation of mono‐ and multi‐species biofilms by mutant cells devoid of gspA was significantly diminished, although planktonic growth of both cell types in the presence of cations was indistinguishable. Because gspA overexpression is lethal to cells lacking gspA and srtA, we performed a genetic screen to identify GspA determinants involving cell viability. DNA sequencing and biochemical characterizations of viable clones revealed that mutations of two critical cysteine residues and a serine residue severely affected GspA glycosylation and biofilm formation. Furthermore, mutant cells lacking gspA were markedly sensitive to sodium dodecyl sulfate, a detergent that solubilizes the cytoplasmic membranes, suggesting the cell envelope of the gspA mutant was altered. Consistent with this observation, the gspA mutant exhibited increased membrane permeability, independent of GspA glycosylation, compared to the wild‐type strain. Altogether, the results support the notion that the cell wall‐anchored glycoprotein GspA provides a defense mechanism against cation stress in biofilm development promoted by A. oris .